A fuzzy logic based recognition technique for RMS variations categorization / Ahmad Faizal Kamal Bahrein - Kamal Bahrein, Ahmad Faizal (2004)
With an increasing usage of sensitive electronic equipment power quality has become a major concern now. One critical aspect of power quality studies is the ability to perform automatic root mean squares (rms) variations data analysis and categorizations. The various data voltage signal variations such as voltage sag, swell, interruption and normal are then classified by a fuzzy logic decision system using the fiizzified values of maximum and the minimum magnitude of the voltage component.